Lexical Analysis of “Domestic Violence Act” of United Kingdom and Pakistan: A Comparative Study - Khaleel, Badriah; Khan, Ameema Ali; Khan, Mahaam (Pakistan Languages and Humanities Review, 2025)
This study is presented to lexically analyze the "Domestic Violence Act" of the United Kingdom (2021) and Pakistan (2020). This comparative study provides similarities, differences, and the portrayal of social actors within the legal framework. The social actors of “Domestic Violence Act” of Pakistan (2020) are analyzed with the help of Social Actor Representation by Van Leeuwan (2008). Qualitative methodology is employed in this study, data from the Acts are examined to discern lexical and predominant features. The study highlights the significance of linguistic analysis in legal discourse, shedding light on societal dynamics shaping domestic violence legislation. This study contributes to forensic linguistics, informing legal professionals, advocacy groups, and policymakers for enhanced legislation and effective implementation in addressing domestic violence. Findings suggest both Acts prioritize victim protection and justice, with divergent gender-inclusive strategies. While the United Kingdom’s Act (2021) adopts a non-gendered approach, Pakistan's Act (2020) explicitly addresses women's vulnerability. Despite efforts for inclusivity, challenges in implementation persist, particularly in patriarchal contexts, impacting justice delivery.